Interleukin 2 induces tyrosine phosphorylation and activation of p72-74 Raf-1 kinase in a T-cell line. - Turner, B (1991)
Interleukin 2 (IL-2) is a lymphokine, produced by T cells upon antigenic or mitogenic stimulation, that is a critical regulator of T-cell proliferation. Although the binding of IL-2 to its receptor has been well characterized, the molecular mechanisms by which IL-2 transmits its signal from the membrane to the interior of the cell are poorly understood. Like most other growth factors, IL-2 causes rapid phosphorylation of proteins within its target cells. Unlike many other growth factors, however, the known subunits of the IL-2 receptor lack tyrosine-specific kinase activity, and little is known about the kinases whose activities are regulated by IL-2. Here we show that IL-2 (but not IL-4) induces rapid phosphorylation of the p72-74 serine/threonine-specific kinase encoded by the c-Raf-1 protooncogene in an IL-2-dependent murine T-cell line, CTLL-2, and that this phosphorylation is associated with increased kinase activity in p72-74 Raf-1-containing immune complexes. The concentration dependence of IL-2-mediated elevations in Raf-1 kinase activity correlated well with IL-2-stimulated proliferation of CTLL-2 cells. Furthermore, much of the IL-2-stimulated phosphorylation of p72-74 Raf-1 occurred on tyrosines. To our knowledge, the Raf-1 kinase represents the first endogenous substrate of an IL-2-regulated tyrosine kinase to be identified.